IDENTIFIKASI PERUBAHAN DASAR LAUT MENGGUNAKAN MODEL DATA BATIMETRI SINGLE BEAM PADA AREA PENAMBANGAN MINERAL BAWAH LAUT - Ryandri Adhinusa, Mohammad
One of the objectives of processing bathymetry data is to obtain surface profiles information of the seabed. These profiles can be used for navigation, offshore activities, research, and underwater mineral mining. In relation to the needs of submarine mineral mining, accurate seabed surface model is important since it is required to calculate the sediment dredging volume, as obtained from the difference elevation values between two surface models of the seabed. This research was attempted to find out how much the difference in the volume of dredging sediment was processed using two different interpolation methods. The processing of bathymetry data for making seabed surface models in this study used Inverse Distance Weighted (IDW) and Kriging interpolation methods. These methods were then applied to two epochs of single beam echosounder batimetric data in November 2017 and March 2018. Based on the results, the dredging volume on the seabed surface model generated using IDW was about 62,299.3 m3. While, the dredging volume generated using Kriging is approximately 72,215.7 m3. The difference on dredging volume is caused by the difference on sample points density between data and surface interpolation mechanism between IDW and Kriging. By calculating and comparing on dredging volume, the dredging cost could be estimated as well as the difference on dredging cost which caused by different interpolation method used.